ANALISIS PENGARUH INTERMEDIASI PERBANKAN, BI RATE, DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI (STUDI JAWA TIMUR PERIODE 2007-2016) - Ditalistya, Risma (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aimed to examine the effect of banking intermediation, inflation, and BI Rate on economic growth in the region of East Java. The author uses economic growth as the dependent variable and include variables of loan to deposit ratio, BI rate, and inflation as an independent variable. The author uses quantitative research methods and using multiple linear regression analysis using OLS during period 2007-2016.The results showed that the variable BI Rate significant and negative influential on economics growth in East Java, while the inflation and loan to deposit ratio influence significantly and positive on economics growth in East Java.Keywords: Economic Growth, Loan to Deposit Ratio, BI Rate, and Inflation